Beyond Taste: Investigating Indoor Air Quality in Sharjah’s Restaurants - Zinah Aldoori (2025)
Indoor Air Quality (IAQ) is crucial for customer satisfaction and well-being in restaurants but is often overlooked. As Sharjah becomes a global gastronomic hub, it is essential to address the complex issues of IAQ, which are linked to health, environmental, and climatic issues. International organizations like ASHRAE and WHO have enacted strict regulations and policies in order for improvement and maintenance of IAQ within the criteria of health and comfort. This study examines toxic air pollutants in a café setting to determine if they meet global requirements and standards. The majority of customers were satisfied with the staff’s service and saw no difference in their work rate, indicating a high standard of indoor air quality which satisfies the United Arab Emirates’ Indoor Air Quality standard.